Report on the practice in industry training in fish preservation. - Flor, Gracia N. (College of Fisheries, University of the Philippines, 1958)
After completing the two years theoretical study on the principles and methods on fisheries, everyone is required to practice the knowledge she had from the instructors who guided her in in her selected line. This is a pre-requisite to every student before she could graduate from the college. Students on fish preservation course have to practice and work in any processing plant touching the following items. That we have to practice on fish canning, refrigeration, smoking, drying, salting, pickling either on the commercial or home use scale.